2019
DOI: 10.1128/aem.01844-19
|View full text |Cite
|
Sign up to set email alerts
|

EpABC Genes in the Adaptive Responses of Exophiala pisciphila to Metal Stress: Functional Importance and Relation to Metal Tolerance

Abstract: Exophiala pisciphila is one of the dominant dark septate endophytes (DSEs) colonizing metal-polluted slag heaps in southwest China. It shows numerous super-metal-tolerant characteristics, but the molecular mechanisms involved remain largely unknown. In the present study, the functional roles of a specific set of ATP-binding cassette (ABC) transporters in E. pisciphila were characterized. In total, 26 EpABC genes belonging to 6 subfamilies (ABCA to ABCG) were annotated in previous transcriptome sequencing librar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Metal detoxification and tolerance mechanisms of microorganisms often include uptake‐reduced, elimination‐enhanced, and intravesicular chelation with metal‐binding proteins and peptides, of which the process is regulated by a rich and complex population of genes (Guo et al, 2016; Priyadarshini et al, 2021). The expression of some uptake‐ and transport‐related proteins is particularly important for fungal HM detoxification, for example, the ATP‐binding cassette transporter EpABC2.1 of E. pisciphila , multidrug, toxic compound extrusion protein MTE1 of Tricholoma vaccinum and major promoter superfamily permease C17235 of Pisolithus albus , which can confer stronger Cd/Cu/Ni tolerance in transformants of Saccharomyces cerevisiae (Ali et al, 2012; Cao et al, 2019; Majorel et al, 2014; Schlunk et al, 2015). However, the molecular mechanisms underlying HM tolerance in fungi remain unclear and will be the focus of future experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Metal detoxification and tolerance mechanisms of microorganisms often include uptake‐reduced, elimination‐enhanced, and intravesicular chelation with metal‐binding proteins and peptides, of which the process is regulated by a rich and complex population of genes (Guo et al, 2016; Priyadarshini et al, 2021). The expression of some uptake‐ and transport‐related proteins is particularly important for fungal HM detoxification, for example, the ATP‐binding cassette transporter EpABC2.1 of E. pisciphila , multidrug, toxic compound extrusion protein MTE1 of Tricholoma vaccinum and major promoter superfamily permease C17235 of Pisolithus albus , which can confer stronger Cd/Cu/Ni tolerance in transformants of Saccharomyces cerevisiae (Ali et al, 2012; Cao et al, 2019; Majorel et al, 2014; Schlunk et al, 2015). However, the molecular mechanisms underlying HM tolerance in fungi remain unclear and will be the focus of future experiments.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid the intracellular accumulation of HM, DSEs can regulate the expression of metal ions transporters and compartmentalize ions through vesicle membrane fusion (Su et al, 2021;Zhao et al, 2015). Upon exposure to Pb and Zn, Exophiala pisciphila (Chaetothyriales) showed a down-regulation of its membrane transporters for the uptake of Zn 2+ , Fe 2+ and Ca 2+ , and up-regulation of transporters involved in the efflux of HM ions from the cytosol, outside a cell or inside vacuoles (Cao et al, 2019;Zhao et al, 2015). Exposure of E. pisciphila and Falciphora oryzae to Cd have revealed the sequestration of Cd 2+ and Zn 2+ in vacuoles and chlamydospores (Liu et al, 2021;Su et al, 2021), as a consequence of the over-expression of SNARE protein Syntaxin 1 involved in chlamydospore formation and vacuole enlargement (Su et al, 2021).…”
Section: Heavy Metal-tolerant Dses Protect Plants From Heavy Metal To...mentioning
confidence: 99%
“…ABC transporters, as one of the largest families of microbial membrane proteins, shows great important in resisting virulence and drug, especially in the function of maintaining metal ion homeostasis by transporting metal ions across the cell membrane in ionic/complex forms [20,21]. It was reported that the expression of 3 ABC genes (EpABC2.1, EpABC3.1, or EpABC4.1) of dominant dark septate endophytes (DSEs) could promote the restoring growth of metal-sensitive mutant by alleviating the inhibitory activity in yeast caused by Pb, Zn and Cd, and further altered toxic ions uptake and accumulation [27]. A specific ABC-transporter of Escherichia coli could mediate the entry of the Fe 2þ bounding siderophores through the inner membrane of the cell from the outer membrane under the help of FepB and FhuD chaperones [28].…”
Section: Mechanisms Of CD Stress Resistance In M Spongiolamentioning
confidence: 99%